Microshells: Photoresponsive Monodisperse Cholesteric Liquid Crystalline Microshells for Tunable Omnidirectional Lasing Enabled by a Visible Light‐Driven Chiral Molecular Switch (Advanced Optical Materials 9/2014). Issue 9 (September 2014) - Chen, Lujian; Li, Yannian; Fan, Jing; Bisoyi, Hari Krishna; Weitz, David A.; Li, Quan
<x xml:space="preserve">Abstract</x> A self‐organized, phototunable 3D photonic superstructure is fabricated from a photoresponsive 1D liquid crystal using microfluidics. On page 845, Q. Li and co‐workers show how the resulting monodisperse microshells are water‐oil‐water double emulsions, in which the oil phase consists of the photoresponsive liquid crystals. The cholesteric microshells exhibit band‐edge lasing in all directions, and the wavelength of the resultant band‐edge laser is tuned via the pumping laser, causing photoisomerization of the chiral molecular switch. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>